Let u=e^(-x)+1
After that it should be easy.
Edit: looking further into this problem, I realized it might not be easy, so I'll give one more hint: when you get the expression for dx in terms of u (think about how you can write e^x in terms of u) and make your substitution, you will end up with a (factored) rational function. At this point you should apply partial fractions to split it into two fractions. THEN it's easy.
Edit 2: After doing some more thinking about the problem, I realized there's a way to avoid the partial fractions: multiply both the numerator and denominator by e^x, then let u=1+e^x. You should then be able to simply cancel the numerator after the subsitution.
2007-01-27 12:59:12
·
answer #1
·
answered by Pascal 7
·
2⤊
0⤋
Integral (2 / (e^(-x) + 1) ) dx
Let u = e^(-x) + 1. Then
u - 1 = e^(-x)
Changing this to logarithmic form,
ln(u - 1) = -x, so
-ln(u - 1) = x
Differentiating both sides,
1/(u - 1) du = dx, so our integral becomes
Integral [ (2 / u) (1/(u - 1)) du ]
Pulling the constant 2 out, we have
2 * Integral [ 1 / (u(u - 1)) ] du
To solve this, we use partial fractions.
1 / [u(u - 1)] = A/u + B/(u - 1)
Multiplying both sides by u(u - 1), we get
1 = A(u - 1) + B(u)
Remember that this is true for ALL values of u.
Let u = 1: Then 1 = A(0) + B(1), so B = 1.
Let u = 0: Then 1 = A(0 - 1) + B(0), so A = -1.
Therefore,
2 * Integral [ 1 / (u(u - 1)) ] du
Is the same as
2 * Integral [ (-1/u) + 1/(u - 1) ] du
Which we can now integrate easily.
2 * [-ln|u| + ln|u - 1|] + C
2 * [ln|u - 1| - ln|u|] + C
But u = e^(-x) + 1, so we have
2 * [ln|e^(-x) + 1 - 1| - ln|e^(-x) + 1|] + C
2 * [ln|e^(-x)| - ln|e^(-x) + 1|] + C
Since ln and e are inverses of each other, ln|e^(-x)| = -x, so
2 * [-x - ln|e^(-x) + 1|] + C
2007-01-27 13:18:58
·
answer #2
·
answered by Puggy 7
·
0⤊
0⤋
If youy positioned lnx = u x=e^u and a million/x dx = du so dx = e^u du so that you get the crucial u^2 *e^u du Integrating through factors = u^2 e^u -2 Int u*e^u du and Int u*e^u du= = u*e^u -Int e^u du = e^u(u-a million) So the outcome is e^u( u^2 -2u +2) = x( (lnx)^2 -2 ln x +2) the same with the second one integrating first e^-5x it is -a million/5 e^-5x
2016-10-16 04:55:53
·
answer #3
·
answered by ? 4
·
0⤊
0⤋
Integrate 2/(e^(-x) + 1) with respect to x.
First, rearrange the terms to make them easier to integrate.
2/(e^(-x) + 1) = 2e^x/(1 + e^x) = 2e^x/(e^x + 1)
∫{2/(e^(-x) + 1)}dx = ∫{2e^x/(e^x + 1)}dx
Let u = e^x + 1
du = e^xdx
2du = 2e^xdx
∫{2e^x/(e^x + 1)}dx = ∫(2/u)du = 2ln(u) + C = 2ln(e^x + 1) + C
No absolute value signs are needed since e^x + 1 is always positive.
2007-01-27 13:35:52
·
answer #4
·
answered by Northstar 7
·
0⤊
0⤋
Have you tried a U substitution? Try letting U = e^(-x)+1, for example...
2007-01-27 13:02:12
·
answer #5
·
answered by Dennis H 4
·
0⤊
1⤋
Use U substitution. :) Generally in U-substitution, you use the more complicated part of the problem, in this case, "e".
2007-01-27 13:03:13
·
answer #6
·
answered by ? 3
·
0⤊
1⤋
right u=1+e^(-x ) then chain rule
2007-01-27 13:03:39
·
answer #7
·
answered by Anonymous
·
0⤊
1⤋